Contrast-enhanced spectral mammography in the evaluation of breast suspicious calcifications: diagnostic accuracy and impact on surgical management. (September 2019) - Houben, Ivo PL; Vanwetswinkel, S; Kalia, V; Thywissen, T; Nelemans, PJ; Heuts, EM; Smidt, ML; Meyer-Baese, A; Wildberger, JE; Lobbes, MBI
Background: Detecting pathological breast calcifications remains challenging. Based on recent studies, contrast-enhanced spectral mammography (CESM) was shown to be superior compared to full-field digital mammography (FFDM). Purpose: To evaluate the diagnostic accuracy of CESM in suspicious breast calcifications and its impact on surgical decision-making. Material and Methods: All screening recalled patients with suspicious calcifications that underwent CESM in the period October 2012 until September 2015 were included. One experienced radiologist provided a BI-RADS classification for the FFDM images only. The evaluation was repeated for the CESM exam. In a simulated tumor board meeting, two breast surgeons decided on the preferred surgical treatment (breast conservation therapy [BCT] versus mastectomy) for all malignant cases. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated defining BI-RADS ≥4 as being malignant. In addition, differences in surgical decision-making were analyzed and compared using McNemar's test. Results: In total, 147 women were included in this study (mean age = 61 years; age range = 49–75 years). Pathology showed 82 benign and 65 malignant lesions, of which 33 were ductal carcinomas in situ and 32 were invasive lesions. Diagnostic performances of CESM (differences compared to FFDM in brackets) were: sensitivity 93.8% (+3%), specificity 36.6% (−2.5%), PPV 54% (0%), and NPV 88.2% (+4%). Based on low-energy images, surgeons suggested BCT in 89% of the cases. Based on the CESM exam, no statistical changes in decisions were observed (86% BCT, P  = 0.453). Conclusion: CESM only slightly improves the diagnostic accuracy of the evaluation of breast calcifications. It is not of added value compared to FFDM in guiding surgical decision-making.